ANALISIS STAKEHOLDER PENGELOLAAN KAWASAN KAKI JEMBATAN SURAMADU SISI MADURA (KKJSM) - M. Husni Tamrin; Agus Wahyudi (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2018)
This study aims to identify and describe the stakeholders involved in the development of the suramadu region based on their influence (Power) and interests (Interest) in the area of the Suramadu Bridge on the Madura side (KKJSM). The method used in this study is a qualitative research method. With the crane technique data obtained by using direct analysis of research objects, namely the government, the public, the private sector that develops the upper area in the area of the suramadu bridge side of Madura (KKJSM). The results in this study show that the stakeholders involved in the development of the Suramadu village side Madura area (KKJSM) consist of primary, key and secondary stakeholders. BP-BPWS which is given the mandate as the implementing agency - the development agency of the suramadu region must be able to work together with stakeholders in reaching the circle. Meanwhile. Main Stakeholders are Community / Villagers who have less power with high interests such as smooth sales and accessibility for visitors and also benefit from visitors who come in the area of the Suramadu Bridge side of Madura (KKJSM). Stakeholders include BPWS as the development of the Surabaya region - Madura which has high intention and high power which also aims for political interests and project interests.Keywords: Potential of Rural, Marine Ecotourism, Tourist Attractions.